Women Negotiating the Boundaries of Justice in Britain, 1300–1700: An Introduction. (October 2019) - Shepard, Alexandra; Stretton, Tim
Abstract: This introduction places the articles featured in this special issue of the Journal of British Studies within the context of recent scholarship on late medieval and early modern women and the law. It is designed to highlight the many boundaries that structured women's legal agency in Britain, including the procedural boundaries that filtered their voices through male advisers and officials, the jurisdictional boundaries that shaped litigation strategies, the constraints surrounding women's appearance as witnesses in court, the gendered differentiation of rights determined by primogeniture and marital property law, and the boundaries between legal and extralegal activity. Emphasizing the importance of a nuanced approach, it rejects the construction of women's litigation simply as a form of resistance to patriarchal norms and also urges caution against overestimating or oversimplifying the choices available to women in legal disputes or their latitude to operate as autonomous individuals. Gender intersected in British courts with locality, resources, jurisdiction, social status, and familial, religious, and political affiliations to inform different women's access to justice, which involved negotiations between unequal actors within various constraints and in complex alignment with multiple and often competing interests.